Flexible Modeling of Emergency Scenarios using Reconfigurable Systems - Hoffmann, Kathrin; Ehrig, Hartmut; Padberg, Julia (Electronic Communications of the EASST, 2009)
In emergency scenarios we can obtain a more effective coordination among team members constituting a mobile ad hoc network (MANET) through the use of reconfigurable systems. This means that cooperative work can be adequately modeled by low level and high level Petri nets with initial markings and the net structure can be adapted to new requirements of the environment during run time by a set of rules. In this paper we give main requirements for flexible processes in MANETs and show how to realize them using the formal notions of reconfigurable systems. The main part presents a case study in the area of emergency management and demonstrates the advantages of our approach which allows the dynamic adaption of processes in mobile environments. In this context we also discuss the main results achieved for reconfigurable systems and outline some interesting aspects of future work.